Analysis Gross Profit Margin and Net Profit Margin at Healthcare Companies Listed in Indonesian Stock Exchange During and Before Covid-19 - Fandy Abdi Darma (Cross-Border Journal of Business Management, 2021)
This study aims to analyze profit level which is projected by Gross Profit Margin and Net Profit Margin and obtained during covid-19 and before covid 19 in 18 healthcare companies listed on the Indonesia Stock Exchange (IDX). The data used in this study are data in 2019 and 2020 (third quarter of each year) on Indonesia Stock Exchange. Data analysis used in this study is descriptive analysis to determine the level of profit projected by Gross Profit Margin and Net Profit Margin incurred from 18 healthcare companies. The results show that there is an increase in Gross Profit Margin and Net Profit Margin during Covid-19 pandemic. This happens because demand for needs related to health for preventing infection of Covid-19 increase.